2014
DOI: 10.1111/bjep.12038
|View full text |Cite
|
Sign up to set email alerts
|

Implicit theories about intelligence and growth (personal best) goals: Exploring reciprocal relationships

Abstract: Background. There has been increasing interest in growth approaches to students' academic development, including value-added models, modelling of academic trajectories, growth motivation orientations, growth mindsets, and growth goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 58 publications
1
27
1
1
Order By: Relevance
“…It is also remarkable the increase in the fixed mindset in the control group. Other longitudinal studies that have analyzed mindsets or goal orientations have not observed such high variability (Martin, 2015, Martin andLiem, 2010), and the period between evaluations of these studies has been greater than ours. Therefore, it is possible that this variability, which was not significant, is due simply to chance, even so, we consider that it would be interesting to carry out longitudinal studies to know the path of the mindsets.…”
Section: Discussioncontrasting
confidence: 67%
“…It is also remarkable the increase in the fixed mindset in the control group. Other longitudinal studies that have analyzed mindsets or goal orientations have not observed such high variability (Martin, 2015, Martin andLiem, 2010), and the period between evaluations of these studies has been greater than ours. Therefore, it is possible that this variability, which was not significant, is due simply to chance, even so, we consider that it would be interesting to carry out longitudinal studies to know the path of the mindsets.…”
Section: Discussioncontrasting
confidence: 67%
“…Such environmental cues may relay a message to women that their ability to succeed in mathematics is limited by group membership, namely their gender (Dweck, , ; Good et al ., ). Indeed, this is an important consideration in view of research indicating that a fixed‐ability mindset may have a deleterious and long‐term effect on educational outcomes (Verniers & Martinot, ; c.f., also Martin, ). Although single‐sex classroom initiatives may have a positive effect by alleviating women's apprehensions about confirming gender‐related stereotypes in the eyes of outgroup members (Picho & Stephens, ; Titze, Jansen, & Heil, ), they may also have a paradoxical effect on mindset.…”
Section: Introductionmentioning
confidence: 93%
“…Whereas previous studies tended to investigate growth in terms of average change across time for groups or cohorts, sustained intra‐individual growth deserves special attention from an educational perspective (Anderman et al ., ; Martin, , ; Martin & Liem, ; Murayama et al ., ). Recent developments in statistical methods, including hierarchical linear modelling (HLM), latent growth modelling (LGM), and multidimensional scaling applied to longitudinal profile analysis (LPAMS), facilitated studies of intra‐individual, as well as interindividual, growth (Anderman et al ., ; Grimm & Ram, ; Muthén & Khoo, ; Shin, , ; Shin et al ., ).…”
Section: Introductionmentioning
confidence: 98%